TINJAUAN YURIDIS TERHADAP PELAKSANAAN PENDAMPINGAN TERSANGKA/TERDAKWA OLEH ADVOKAT DALAM PRAKTEK PENANGANAN PERKARA PIDANA - SUPARMAN, SUPARMAN (Dinamika Hukum, 2018)
The purpose of this study is to get an understanding of the implementation of assistance of suspects/defendants by advocates in the handling of criminal cases and obstacles. The research method consists of: the type of research is sociological juridical, the nature of research is descriptive. Research data include primary and secondary data, Data analysis is done normatively qualitative. The results showed that the implementation of criminal case assistance by the Legal Counsel was conducted based on Law No.8 of 1981 on Criminal Procedure Law. At the level of investigation advocate accompanying the suspect by way of seeing and hearing the examination. At the prosecution level the case was carried out at the time of the second stage submission (the suspect's submission and evidence). On examination at the district court level, in practice the legal counsel is entitled to file an objection to the indictment, to bring witnesses to lighten the defendant, have the right to ask the witness, and the right to file a defense. The barrier that exists in practice is that advocates can not give enough input to defend because they can only see and hear the examination. In the district court, the obstacle faced is a dilemmatic situation, especially in the case of the exercise of the right to file an objection to the indictment. If this right is used the risk is that the trial will be longer because there are several trial delays. If this right is used the process takes a long time so the case is not immediately completed. Keywords: Juridical Review, Advocate, Handling Of Criminal Cases.